Risiko Penyakit Kulit Akibat Kerja di Perusahaan Perkebunan dan Pengolahan Karet - Ahyanti, Mei; Purwono, Purwono (Jurnal Kesehatan, 2019)
Skin disease is a disease that attacks the body's surface and is caused by a variety of causes. PTPN VII Business Unit Way Berulu Regency Pesawaran, Lampung company plantation, and rubber/ latex. The length of time required in the processing and the addition of chemical substances at risk against the workers. The research aims to know the risk factors of occupational skin disease occurrences in PTPN VII Business Unit Berulu Way, using design case control with the total sample as many as 73 cases and 73 controls so that the total sample is 146 people, held on June-October 2017. The determination of cases based on Medical Records that are in the health service center of the plantation (Puskesbun). The analysis is done in univariate, and bivariate using Chi-Square test. The results of the analysis concluded that there was a significant relationship between previous skin disease history (pv=0,000, OR=4,399, 95% CI=1,995-9,698), personal hygiene (pv=0,000, OR=4,100, 95% CI = 1,953 - 8,608), supply of clean water (pv=0.020, OR=2.304, 95% CI=1.187-4.472) and use of APD (pv=0.037, OR=2.177, 95% CI=1.123-4.220) with the incidence of skin diseases due to work.